Dampak Minuman Keras Mempengaruhi Kualitas Hidup Jemaat Efrat Gereja Bethel Indonesia (GBI) di Kota Kupang - Filmon Manafe; Yunus Manafe; Yusup Rogo Yuono (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Liquor (Sopi) is a drink that contains alcohol which is fermented from brown sugar or granulated sugar and the roots of the herb are mixed together and then distilled. If consumed excessively it will cause bad things to both physical and spiritual health. Alcohol can also make someone lose consciousness because they consume too much. Apart from that, behavior and thinking are chaotic, causing commotion or quarrels which result in victims. This is part of the abuse of alcoholic drinks among local congregations and continues to increase from year to year. Community members in the city of Kupang have a habit of consuming alcoholic drinks every day and also at large events such as traditional events, weddings, Christmas and New Year. The church is here to provide solutions or directions to the congregation not to consume alcoholic drinks.